PENGARUH TINGKAT KECUKUPAN MODAL (CAR), RISIKO PEMBIAYAAN (NPF), DAN EFISENSI OPERASIONAL (BOPO) TERHADAP PROFITABILITAS (ROA) PADA BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA - Nurul Innayah; Achmad Fauzi; Indah Muliasari (Yayasan Education and Social Center, 2023)
This study aims to determine the effect of Capital Adequacy Ratio, Financing Risk and Operational Efficiency on Profitability in Islamic People's Financing Banks in Indonesia. The research method used is a quantitative method. Data collection was carried out using documentation techniques and secondary data collection from the BPRS financial reports at website Financial Services Authority (OJK) for the 2019-2021 period. The sample in this study uses purposive sampling technique with a total sample of 64 BPRS. This study used several data analysis techniques, namely descriptive statistical analysis, panel data regression analysis, classical assumption test and hypothesis testing. Based on the partial results of the study, the level of capital adequacy and operational efficiency has a significant negative effect on profitability. Meanwhile, financing risk has no effect on profitability. The coefficient of determination in this study is 72.79% which indicates the ability of the level of capital adequacy, financing risk and operational efficiency in explaining the effect to profitability